Short-term antidepressant administration reduces negative self-referential processing in the medial prefrontal cortex in subjects at risk for depression - Di Simplicio, M; Norbury, R; Harmer, C (2012)
Depression has been associated with changes in responses within the medial prefrontal cortex (mPFC) during emotional information processing. Antidepressant drug treatment has been shown to modify neural responses in healthy volunteers early in treatment within similar circuitry. It is unclear, however, whether the same early effect occurs in depressed patients, before changes in mood. The current study therefore investigated the effects of 7-days administration of the selective serotonin-uptake inhibitor citalopram vs placebo in volunteers (n29) at a high risk for the development of depression, using the personality phenotype of high neuroticism in a double-blind, between-groups design. On the last day of treatment, resting haemoperfusion and functional magnetic resonance imaging (MRI) data were acquired during a self-referential words categorisation task. A significant activation in a cluster of mPFC areas, including dorsal anterior cingulate and right orbitofrontal cortex was revealed, driven by decreased responses to the negative self-descriptors following citalopram compared with placebo, in the absence of any mood differences. These findings show a normalisation of neural abnormalities in-and at-risk population early in treatment, supporting the theory that antidepressants may indeed act by modifying specific neural dysfunctions correlated to negative cognitive biases. © 2012 Macmillan Publishers Limited All rights reserved.